Pomiguyeva L. P. Semantic relations of English terminology wordbuilding elements - Pomiguyeva L. P. (Philological Treatises, 2020)
The author of the article deals with the nature of "terminologic word–combinations", examines the scientific and technical terms concept system structure taking into account their linguistic features. The models of word–combination terminology classification and their meanings are described in the English terminology system development process.